Efforts to increase the value of salak products in Wonokerto Village, Sleman - Muhaimin Muhaimin; Tatang Shabur Julianto; Rheyza Virgiawan (Universitas Muhammadiyah Magelang, 2023)
Salak is a prominent agricultural commodity in the Sleman Region, particularly in Wonokerto Village, Turi District. Residents of Wonokerto continue to rely on salak as a source of income, selling it in its fresh fruit form. However, salak farmers currently face a challenge with the declining selling value of their produce, especially during the main harvest season. Salak with a low selling value tends to go unsold and may end up rotting. The objective of this community service activity is to increase the added value of processed salak products, such as salak fruit vinegar, and provide licensing assistance for effective marketing. The community service activities are divided into two parts: learning and mentoring. The results of the activity demonstrate that residents can successfully produce salak fruit vinegar. Participants showed great enthusiasm and interest in making salak vinegar, with 44.44% expressing high satisfaction with the training. The salak vinegar product has received certification with P-IRT number 1093404011436-28 and Business Identification Number (NIB) 1610230086544.